Pengaruh Influencer Review dan Product Ingredients Terhadap Perilaku Konsumen pada Product Hydrasoothe Azarine Sunscreen Gel di Surabaya - Via Aldina Auva; Nirawati, Lia (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the influence of influencer reviews and product ingredients of Hydrasoothe Azarine Sunscreen Gel in Surabaya. This type of research is associative using a quantitative approach. The population is users who are familiar with the influencer review “Tasya Farasya” and use product ingredients in Hydrasoothe Azarine Sunscreen Gel products in Surabaya, with a sample of 120 respondents. The sampling technique used was non-probability sampling with a purposive sampling approach, while the data collection technique was carried out through a questionnaire. Data analysis was performed using multiple linear regression. The results of the analysis show that both independent variables have a positive influence on consumer behavior. Simultaneously, influencer review and product ingredients have a significant effect on consumer behavior. In addition, it is partially stated that influencer reviews on consumer behavior have a significant effect and product ingredients partially have a significant effect on consumer behavior. Internal factors that can influence consumer behavior on Hydrasoothe Azarine Sunscreen Gel products in Surabaya are that the majority are female, the age range is 15-24 years old who live precisely in West Surabaya, income < Rp 1,000,000, senior high school, and have perceptions because the sunscreen is quality. This states that the importance of influencer reviews and product ingredients in shaping consumer opinions and perceptions of a product.